Portofolio Efisien Model Markowitz dengan Kendala Proporsi Aset Positif dan Target Return yang Ditentukan - Nurwahidah; Hasan, Asriani; MA, Ratnah Kurniati (Journal of Mathematics, Computations and Statistics, 2023)
Rational investors tend to diversify their asset for reducing investment risk. Markowitz portfoliomodel can be an investment strategy to minimize risk and maximize return of investment. This studyestablishes the Markowitz model portfolio with positive asset weight constraints and determined targetreturns. Quadratic programming is an approach used to determine the proportion of each stock in theportfolio. Therefore, 5 efficient portfolios with less risk level than individual stocks are obtained. Theresults of the performance measurement stated that the portfolio with asset centered proportion on BYANhad the best performance. It is due to the high expected returns and low level of risk measurement.